A Randomized Trial of Azithromycin Versus Amoxicillin for the Treatment of Chlamydia trachomatis in pregnancy. Issue 4 (2001) - Kacmar, Jennifer; Cheh, Emily; Montagno, Andrea; Peipert, Jeffrey F.
Abstract : Objective: To compare the compliance, side effects and efficacy of amoxicillin and azithromycin for the treatment of Chlamydia trachomatis infection in pregnancy. Methods: This is a randomized single-blind trial of women diagnosed with C. trachomatis before 33 weeks gestation.Women were randomly assigned either 500 mg amoxicillin orally three times per day for 7 days or a single dose of 1 g azithromycin orally. Patientswere interviewed by telephone approximately 3–7 days following therapy to assess compliance and side effects. Test of cure was performed at a follow-up visit 4–6 weeks following completion of therapy. Results: Thirty-nine patients were randomized with 19 receiving amoxicillin and 20 receiving azithromycin. There were no differences in baseline data between the two groups, and there were no statistically significant differences in side effects, compliance or efficacy. In the amoxicillin group 84% of women took all pills, while 100% completed the single 1 g dose of azithromycin. Side effects were common in both groups (38% overall), with 40% of the azithromycin group reporting moderate to severe gastrointestinal side effects compared to 17% in the amoxicillin group ( p = 0.11). Of patients who returned for follow-up test of cure, 3 of 15 (20%) in the amoxicillin group were positive compared with 1 of 19 (5%) in the azithromycin group ( p = 0.3). Conclusions: Side effects of therapy for C. trachomatis in pregnancy are common. Amoxicillin was slightly better tolerated than azithromycin. Compliance and cure rates with both regimens was high.